Spontaneous middle lobe torsion: An institutional case seriesCentral MessagePerspective - Britton B. Donato, MD, MPH, MS; Marisa Sewell, MD; Hasan Al Harakeh, MD; Ayan Sen, MD, MSc; Bhavesh M. Patel, MD; Paige Morgan, PA-C, MS; Amit K. Mathur, MD, MS; Adyr A. Moss, MD; Winston R. Hewitt, MD; Megan E. Campany, BS; Megan M. Dulohery Scrondin, MD; Stephen D. Cassivi, MD, MSc; et al. (JTCVS Techniques)
Objective: Lobar torsion is a rare occurrence in which a portion of the lung is twisted on its bronchovascular pedicle. The vast majority are observed in the acute postoperative period often following right upper lobectomy. Spontaneous middle lobe torsion independent of pulmonary resection is exceptionally rarer; fewer than 15 cases have been recorded. We present an institutional case series of 2 patients postorthotopic liver transplantation who developed spontaneous middle lobe torsion due to large pleural effusions. Methods: We provide the medical course as well as intraoperative techniques for our 2 patients along with a review of the literature. Results: Both patients in this case series underwent orthotopic liver transplant complicated postoperatively by a large pulmonary effusion. Patient one developed an abdominal hematoma requiring evacuation and repair, after which he developed progressive shortness of breath. Bronchoscopy revealed a right middle lobe obstruction; upon thoracotomy, 180-degree torsion with widespread necrosis was evident and the middle lobe was removed. He is doing well to date. Patient 2 experienced postoperative pleural effusion and mucus plugging; computed tomography revealed abrupt middle lobe arterial occlusion prompting urgent operative intervention. Again, the middle lobe was grossly ischemic and dissection revealed a 360-degree torsion around the pedicle. It was resected. He is doing well to date. Conclusions: As the result of its rarity, radiographic and clinical diagnosis of spontaneous pulmonary lobar torsion is challenging; a high index of suspicion for spontaneous middle lobe torsion must be maintained to avoid delays in diagnosis. Prompt surgical intervention is essential to improve patient outcomes.